The effect of instrumental stray light on Brewer and Dobson total ozone measurements - O. Moeini; O. Moeini; O. Moeini; Z. Vaziri Zanjani; C. T. McElroy; D. W. Tarasick; R. D. Evans; I. Petropavlovskikh; K.-H. Feng (Atmospheric Measurement Techniques, 2019)
Dobson and Brewer spectrophotometers are the primary, standard instruments for ground-based ozone measurements under the World Meteorological Organization's (WMO) Global Atmosphere Watch program. The accuracy of the data retrieval for both instruments depends on a knowledge of the ozone absorption coefficients and some assumptions underlying the data analysis. Instrumental stray light causes nonlinearity in the response of both the Brewer and Dobson to ozone at large ozone slant paths. In addition, it affects the effective ozone absorption coefficients and extraterrestrial constants that are both instrument-dependent. This effect has not been taken into account in the calculation of ozone absorption coefficients that are currently recommended by WMO for the Dobson network. The ozone absorption coefficients are calculated for each Brewer instrument individually, but in the current procedure the effect of stray light is not considered. This study documents the error caused by the effect of stray light in the Brewer and Dobson total ozone measurements using a physical model for each instrument. For the first time, new ozone absorption coefficients are calculated for the Brewer and Dobson instruments, taking into account the stray light effect. The analyses show that the differences detected between the total ozone amounts deduced from Dobson AD and CD pair wavelengths are related to the level of stray light within the instrument. The discrepancy introduced by the assumption of a fixed height for the ozone layer for ozone measurements at high latitude sites is also evaluated. The ozone data collected by two Dobson instruments during the period of December 2008 to December 2014 are compared with ozone data from a collocated double monochromator Brewer spectrophotometer (Mark III). The results illustrate the dependence of Dobson AD and CD pair measurements on stray light.